Systematic review of acupuncture to improve ovarian function in women with poor ovarian response - Wang, Rong-Rong; Su, Meng-Hua; Liu, Li-Ying; Lai, Yuan-Yuan; Guo, Xiao-Li; Gan, Di; Zheng, Xiao-Yan; Yang, Han; Yu, Si-Yi; Liang, Fan-Rong; Wei, Wei; Zhong, Ying; et al. (Frontiers in Endocrinology, 2023)
Abstract Objective: To determine the effect of acupuncture in treating poor ovarian response (POR). Methods: We searched MEDLINE (via PubMed), EMBASE, Allied and Complementary Medicine Database, CNKI, CBM, VIP database, Wanfang Database, and relevant registration databases from inception to January 30, 2023. In this review, both Chinese and English peer-reviewed literature were included. Only randomized controlled trials (RCTs) using acupuncture as an intervention for POR patients undergoing in vitro fertilization were considered. Results: Seven clinical randomized controlled trials (RCTs) were eventually included for comparison (516 women). The quality of included studies was generally low or very low. For the meta-analysis, seven studies showed that compared with controlled ovarian hyperstimulation (COH) therapy, acupuncture combined with COH therapy could significantly increase the implantation rate (RR=2.13, 95%CI [1.08, 4.21], p=0.03), the number of oocytes retrieved (MD=1.02, 95%CI [0.72, 1.32], p＜0.00001), the thickness of endometrium (MD=0.54, 95%CI [0.13, 0.96], p=0.01), and the antral follicle count (MD=1.52, 95%CI [1.08, 1.95], p＜0.00001), reduce follicle-stimulating hormone (FSH) levels (MD=-1.52, 95%CI [-2.41, -0.62], p=0.0009) and improve estradiol (E2) levels (MD=1667.80, 95%CI [1578.29, 1757.31], p＜0.00001). Besides, there were significant differences in the duration of Gn (MD=0.47, 95%CI [-0.00, 0.94], p=0.05) between the two groups. However, no statistical variation was observed in improving clinical pregnancy rate (CPR), fertilization rate, high-quality embryo rate, luteinizing hormone (LH) value, anti-mullerian hormone (AMH) value, or reducing the dose of gonadotropin (Gn) values between the acupuncture plus COH therapy group and the COH therapy group. Conclusion: Acupuncture combined with COH therapy is doubtful in improving the pregnancy outcome of POR patients. Secondly, acupuncture can also improve the sex hormone level of POR women, and improve ovarian function. Furthermore, more RCTs of acupuncture in POR are needed to be incorporated into future meta-analyses. PROSPERO registration number: CRD 42020169560. Keywords: acupuncture, poor ovarian response, ovarian function, in vitro fertilization, systematic review.